Direct recovery of papain from papaya juice using expanded bed adsorption chromatography - He, Yu Hai (2013)
Papain is an enzyme from Carica papaya which of great research interest in recent years due to its pharmaceutical and biological application. The adsorption of papain on AmberliteTM XAD7HP adsorbent with the mechanism of reverse phase liquid chromatography (RPLC) was investigated in this study. The equilibrium adsorption isotherm, binding buffer and elution buffer conditions were studied in a batch system. 15% ethanol was obtained as the optimum binding buffer with binding efficiency of 76.53% and 40% ethanol was confirmed as the optimum elution buffer with elution efficiency of 84.09%. At the optimum conditions, the adsorption capacity of AmberliteTM XAD7HP for papain was found to be 4.5 mg papain/g adsorbent. The equilibrium isotherm was fitted to Freundlich isotherm which has an n value of 1.3927 and the K of the adsorption of papain onto the AmberliteTM was 267.67 (mg/g)(ml/mg)n, R2 is 0.9746. Papain in the concentrated extract was purified 4.3-folds and 55% purity corresponding to around 15% of the total papain in the crude juice. More than 84% of the adsorbed papain was eluted using 40% ethanol as the elution buffer. The efficiency of purifying papain from papaya juice using the method developed above was around 65.5%. A purified papain with 65% yield and 50% purity was recovered. A direct recovery of papain enzyme from unclarified Carica papaya juice was developed successfully using a reversed phase expanded bed adsorption chromatography (RP-EBAC). The dynamic binding capacity for the RP-EBAC at 10% breakthrough of 810.52 μg papain/g adsorbent was achieved at a linear flow velocity of 936 cm/h, bed expansion degree of 2 and feedstock viscosity of 2.68 mPa·s. Papain purity of 58.39% and purification factor of 4.96 was obtained by one-step elution in RP-EBAC. Two-step elution was employed to enhance the purity of papain in RP-EBAC which gives higher papain purity of 74.98% and higher purification factor of 7.04. Absolute ethanol (100%) was successfully used in the Clean-in-place (CIP) for cleaning of the AmberliteTM XAD7HP adsorbent. After the first CIP about 15% of total protein was still retained on the adsorbent and about 3% of total protein still retained on the adsorbent after second CIP. It shows that there is no strong cumulative effect of contaminants happens on the adsorbent. This work shows a great potential of using RP-EBAC to purify papain from unclarified Carica papaya juice.